2022
DOI: 10.1002/eji.202149596
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus patients contain B‐cell receptor repertoires sensitive to immunosuppressive drugs

Abstract: Immune repertoire (IR) during treatment may be a surrogate biomarker for disease response. Changes of the IR in systemic lupus erythematosus patients in response to immunosuppressive drugs were identified in ten SLE patients. Patients provided peripheral blood mononuclear cells at two time points for sequencing. They were divided into sensitive and nonsensitive groups by their clinical responses to immunosuppressive drugs. After treatment, the BCR expression significantly decreased in patients from the sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
3
2
0
Order By: Relevance
“…Wardemann and Mefre previously showed that a longer immunoglobulin heavy chain CDR3 correlates with antibody autoreactivity in SLE ( 49 , 50 ). We found that no significant difference in CDR3 mean length of IGHV in BAFF-R-Fc-treated mice compared to those observed in controls, consistent with a previous study ( 47 ). However, the distribution of CDR3 lengths was altered, with the most commonly used length decreasing from 15 amino acids to 14 amino acids.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Wardemann and Mefre previously showed that a longer immunoglobulin heavy chain CDR3 correlates with antibody autoreactivity in SLE ( 49 , 50 ). We found that no significant difference in CDR3 mean length of IGHV in BAFF-R-Fc-treated mice compared to those observed in controls, consistent with a previous study ( 47 ). However, the distribution of CDR3 lengths was altered, with the most commonly used length decreasing from 15 amino acids to 14 amino acids.…”
Section: Discussionsupporting
confidence: 92%
“…As we found the BCR diversity and richness were positively correlated with B cells proportion. Similar outcomes have been reported in patients receiving stable immunosuppressive therapy such as mycophenolate mofetil and leflunomide ( 47 ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Compared with those from healthy donors, B cells from SLE patients show increased BCR clonotypes and biased usage of BCR V(D)J genes [ 139 ]. In particular, B cells from SLE patients who are sensitive to immunosuppressive drugs show significantly decreased BCR expression and clonal diversification, while these changes are undetectable in nonsensitive lupus patients, indicating that alterations of the BCR repertoire are associated with sensitivity to immunosuppressive therapy [ 140 ]. It has also been reported that the nonresponse rates to rituximab among RA patients are closely associated with marked disruption of the BCR repertoire, suggesting that BCR clonality may serve as a predictor of the responses of RA patients to B-cell-depletion therapy [ 141 ].…”
Section: Epigenetic Dysregulation Of B Cells In Autoimmune Diseasesmentioning
confidence: 99%
“…1). Identifying B cell receptors (BCRs) that respond to specific antigens is an important goal for describing the dynamics of B cell immunity following vaccination, with potential applications in vaccine development [1][2][3][4][5][6], personalized medicine [7][8][9], and antibody-derived therapeutics [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%